Estimating Trade Equations from Aggregate Bilateral Data - Bayoumi, Tamim (Washington, D.C. : International Monetary Fund, 1999)
This paper uses bilateral data on 420 merchandise trade flows between 21 industrial countries are used to estimate standard trade equations. The data set of over 11,000 observations allows the underlying elasticities to be estimated with considerable precision. Remarkably, a single specification appears to explain behavior across these countries in spite of the large number of individual flows analyzed. The results indicate a powerful long-run effect from supply on exports. Also, the real exchange rate elasticity depends upon the behavior of third country exchange rates. There is evidence of pricing to market and of a J-curve.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet